2009
DOI: 10.1016/j.soilbio.2009.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Tree girdling provides insight on the role of labile carbon in nitrogen partitioning between soil microorganisms and adult European beech

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
173
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 179 publications
(186 citation statements)
references
References 57 publications
12
173
1
Order By: Relevance
“…Soil nitrogen was relatively stable (total N, 7.7 Ϯ 0.7 and 8.6 Ϯ 0.6 mg g Ϫ1 soil [dry weight] on girdled and control plots, respectively; dissolved organic N, 29 Ϯ 6 and 32 Ϯ 6 g g Ϫ1 soil [dry weight] on girdled and control plots, respectively), whereas dissolved organic carbon was lower in soil from the girdled plots than in that from nongirdled plots (16). HЈ was positively correlated with DOC/DON (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Soil nitrogen was relatively stable (total N, 7.7 Ϯ 0.7 and 8.6 Ϯ 0.6 mg g Ϫ1 soil [dry weight] on girdled and control plots, respectively; dissolved organic N, 29 Ϯ 6 and 32 Ϯ 6 g g Ϫ1 soil [dry weight] on girdled and control plots, respectively), whereas dissolved organic carbon was lower in soil from the girdled plots than in that from nongirdled plots (16). HЈ was positively correlated with DOC/DON (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our experiment, we used an NH 4 þ concentration similar to that found in the Tuttlingen forest (Dannenmann et al, 2009), where the soil for beech mycorrhizal inoculation was sampled. The beech trees in the Tuttlingen forest are colonized by a characteristic EMF flora, including all species present in this study (Buée et al, 2005;Pena et al, 2010;.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 120 mycorrhizal and 120 non-mycorrhizal beech seedlings were transplanted without adherent soil individually into 660 ml pots with a sand-peat mixture and supplied daily with 56 ml of nutrient solution containing 0.4 mM NH 4 þ as the sole N source. This concentration was chosen because it was similar to that in forest soil of the Tuttlingen site (Dannenmann et al, 2009) Jongbloed et al, 1991;Eltrop and Marschner, 1996) and because preceding analysis with attached beech roots at the Tuttlingen site showed saturation of NH 4 þ uptake at concentrations above 0.05 mM (Gessler et al, 2005). The seedlings were grown either in full light (200 mmol PAR m À 2 s À 1 ) or in the shade (35-40 mmol PAR m À 2 s À 1 at plant height).…”
Section: Plant Cultivation and Experimental Treatmentsmentioning
confidence: 99%
“…Hö gberg et al (2007) observed a tendency towards higher inorganic N levels in girdled plots of a boreal forest, whereas Ekberg et al (2007) detected a decrease in total organic C in girdled plots of temperate spruce stand. It is thus likely that girdling-related changes in soil chemistry, in particular labile C and N pools have considerable effects on the soil microbial community structure (Dannenmann et al, 2009;Weintraub et al, 2007).…”
Section: Introductionmentioning
confidence: 99%